2018
DOI: 10.5935/1984-0063.20180005
|View full text |Cite
|
Sign up to set email alerts
|

Sleep respiratory disturbances during the ascent to Mount Aconcagua

Abstract: IntroductionMountaineers exposed to hypobaric hypoxia (HH) show high-altitude periodic breathing (PB).ObjectiveTo analyze high-altitude PB during the ascent of Mount Aconcagua (Argentina).Materials and MethodsDescriptive study in healthy volunteers using respiratory polygraphy (RP) at different altitudes.ResultsWe studied 8 andinist, mean age: 36 years old (25-51), body mass index (BMI) of 23.6 (20.9-28.7) and 22.77 (20.9-27.7) upon return, p<0.01. RP without PB showed a lower Oxygen Desaturation Index (ODI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
1
6
1
Order By: Relevance
“…Sleep Awak did not change in any of the groups during STG in this study. These results are consistent with others that reported no change in sleep arousals or awakenings up to 4500 m (Ortiz‐Naretto et al, 2018; Rojc et al, 2014) but differs from others that reported increased awakenings above 3000 m (Beaumont et al, 2007; Tseng et al, 2015). The lack of consistency between studies in regards to sleep arousals is not well understood but may be related to the controversy over whether periodic breathing results in awakenings (Ainslie et al, 2013; Bloch et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Sleep Awak did not change in any of the groups during STG in this study. These results are consistent with others that reported no change in sleep arousals or awakenings up to 4500 m (Ortiz‐Naretto et al, 2018; Rojc et al, 2014) but differs from others that reported increased awakenings above 3000 m (Beaumont et al, 2007; Tseng et al, 2015). The lack of consistency between studies in regards to sleep arousals is not well understood but may be related to the controversy over whether periodic breathing results in awakenings (Ainslie et al, 2013; Bloch et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Although wrist actigraphy and pulse oximetry were used to assess sleep quality and quantity, sleep measurements using these devices demonstrate a high correlation with polysomnography measurements (Latshang et al, 2016;Nussbaumer-Ochsner et al, 2011). Studies that have employed polysomnography to study sleep at altitudes similar to the ones utilized in this study have reported an increase in desaturation events at ~3500 m (Beaumont et al, 2007;Fischer et al, 2004;Heinzer et al, 2016;Kohler et al, 2008) and above (Nussbaumer-Ochsner et al, 2012;Orr et al, 2018) with no differences observed below this altitude (Latshang et al, 2013;Ortiz-Naretto et al, 2018). In this study, sleep DeSHr were only increased in the 4300 m group during STG which differs from our hypothesis that both the 3500 and 4300 m groups would experience a greater number of these events.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The prevalence of SAS (CSA and OSA) significantly increased with rising elevation in our study. Ortiz-Naretto et al ( 23 ) reported that no mountaineers had periodic breathing (PB) at sea level, but that PB was frequent above 2,581 m and occurred in all subjects above 4,900 m. Liu et al ( 24 ) demonstrated that newcomers who ascended to HA above 2,500 m often developed sleep-disorder breathing (SDB), manifesting as SAS, PB, and nocturnal hypoxemia, which can weaken already exhausted climbers. The above studies showed that acute exposure to high altitudes can damage sleep and breathing in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It can be triggered by hypoxaemia and hypocapnia occurring during sleep, altitude exposure, stroke, heart failure 3 and interstitial lung disease. 4 This phenomenon has previously been described in hypobaric hypoxia during exercise 5 and sleep 6 and, experimentally, in normobaric hypoxia in healthy young adults and athletes. 7 8 Guidelines indicate supplemental oxygen if there is a fall in SpO 2 below 85% or the use of continuous positive airway pressure (CPAP) devices in patients with already diagnosed sleep disturbances requiring them.…”
mentioning
confidence: 57%